Estado e planejamento educacional no contexto do federalismo: o processo de elaboração dos planos municipais de educação em Goiás - Alves, Edson Ferreira (2020)
The present thesis’ main objective is to study the elaboration process of the Municipal Education Plans (or Planos Municipais de Educação, PMEs), considering the involvement of the political society and of civil society to the end of this research, understanding them as a State policy. As the selection criteria determined, the cities chosen were of Itaberaí (Central Goiás Mesoregion), Luziânia (East Goiás), Minaçu (North Goiás), São Miguel do Araguaia (Northwest Goiás) e Silvânia (South Goiás). Methodologically, the investigation was configured as a case study developed as a converging parallel project of mixed methods, outlining as qualitative sources documents and interview with the coordinators of the commissions of elaboration of the PMEs. As quantitative sources, the resources were the application of questionnaires with other members of the commissions. The theoretical basis for analysis was the concept of State (political society plus civil society) by Antonio Gramsci, which situated the elaborating of the PMEs, as well as the interstate sets instituted in the context of the Brazilian federalism, which should become effective by the means of a cooperative regime. Municipal documents were situated in the context of educational planning and its variations, by means of the historical course of this strategy throughout the entire republican period. As a final focus point, this thesis presents two National Education Plans approved by law, the PNE 2001-2010 and the PNE 2014-2024. The latter, materialized in the law nº13.005/2014, determined that the subnational entities approved the correlated ten-year-plans within a year, according to the national document (article 8º). This imperative, by means of the cooperative action of the Articulation Secretary with the Teaching Systems/Ministry of Education (Sistemas de Ensino/Ministério da Educação - Sase/MEC), was the motivator for the municipalities to elaborate their PMEs. The framework of this research’s analysis is based in authors such as Abrúcio (2010), Araújo (2010), Bordignon (2014), Buci-Glucksmann (1980), Coutinho (1992, 2006), Cueto and Guardamagna (2012), Cury (2009, 2010, 2015), Dourado (2011, 2013, 2017), Gramsci (1999, 2004a, 2004b, 2007), Horta (1982, 1997), Matus (1993) and Saviani (2007, 2014, 2016a). The data indicate difficulties in mobilization of civil society and also on political society to participate in the elaboration of the PMEs, also indicate short deadlines for its implementation, as well as the overwhelming use of the materials produced by Sase/MEC and the PNE 2014-2024 itself as references to the municipal coordinations. About the management of these commissions, it became evident in a systematic and organized way, with distinct dynamics effectuated in each case, but with a similar standard of referrals and operationalization, the management focus on the representatives of the Municipal Secretaries of Education. It means to focus on the political society, using democratic and participative indicators, with its limitations and contradictions. It is identified as a challenge to the municipalities the materialization of the PMEs as a State policy, in a scenery where the PNE 2014-2024 itself has been put in the secondary plan because of neoliberal policies of budget restriction and because of the Constitutional Amendment nº 95/2016.